2016
DOI: 10.1016/j.fertnstert.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNAs as diagnostic markers of endometriosis: a comprehensive array-based analysis

Abstract: We identified several miRNAs in serum that distinguished subjects with endometriosis from those without. miR-125b-5p had the greatest potential as a single diagnostic biomarker. A combination of that miRNA with miR-451a and miR-3613-5p further improved diagnostic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
175
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(194 citation statements)
references
References 48 publications
12
175
2
5
Order By: Relevance
“…The inverse relationship between the expression of miRNAs and their target genes is complex and evolving. There is accumulating data that miRNAs contribute to the pathogenesis of endometriosis by regulating abnormal cell differentiation, invasion, and inflammation 23. It has been reported that the expression of several miRNAs differs between the eutopic and ectopic endometrial tissues of women with and without endometriosis 9, 24.…”
Section: Discussionmentioning
confidence: 99%
“…The inverse relationship between the expression of miRNAs and their target genes is complex and evolving. There is accumulating data that miRNAs contribute to the pathogenesis of endometriosis by regulating abnormal cell differentiation, invasion, and inflammation 23. It has been reported that the expression of several miRNAs differs between the eutopic and ectopic endometrial tissues of women with and without endometriosis 9, 24.…”
Section: Discussionmentioning
confidence: 99%
“…For example, let-7g and miR-221 levels showed a positive correlation with the progression of metabolic diseases in female patients [74]. Additionally, events like menstrual cycles [7578] and pregnancy [79, 80] also altered the overall circulating miRNA profile. For example, the levels of miRNAs from a chromosome 14 and 19 miRNA clusters significantly increased during pregnancy [81].…”
Section: Factors Affect the Spectrum Of Extracellular Rnamentioning
confidence: 99%
“…In studying this process it has been revealed that microRNAs (miRNAs) are pivotal in this. MicroRNAs are intronic coded genes implicated in regulating gene expression and thus fundamentally control biological systems through gene silencing of several mRNAs simultaneously [14]. Through improvements in next generation sequencing and microarray technology we are now able to study the effects of miRNAs at a genomic scale.…”
Section: Invest Gynecol Res Women's Health Investigations In Gynecolomentioning
confidence: 99%
“…Through improvements in next generation sequencing and microarray technology we are now able to study the effects of miRNAs at a genomic scale. Furthermore, the presence of circulating miRNA in the blood has led to research into their application as biomarkers in several conditions including sepsis and myocardial infarction [14]. Early research in this field has revealed differential miRNA expressions between endometrial patients and controls with downregulation of miR-34C-5p, miR-9 and mir-34b, let-7d etc.…”
Section: Invest Gynecol Res Women's Health Investigations In Gynecolomentioning
confidence: 99%
See 1 more Smart Citation